E-MODUL BERBASIS PENDEKATAN JAS (JELAJAH ALAM SEKITAR) PADA MATERI LARUTAN ELEKTROLIT DAN NON ELEKTROLIT UNTUK MENDUKUNG LITERASI SAINS SISWA - Wiyandika, Luthfia; Refelita, Fitri (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2025)
This research was motivated by students’ difficulties in understanding the concepts of electrolyte and nonelectrolyte solution material, and there is no E-module based on JAS (explore the nature around) approach in supporting student science literature on electrolyte and non-electrolyte solution materials. This research aimed at knowing the practicality and validity of E-module module based on JAS (explore the nature around) approach. This research was conducted at state senior high school 1 Pekanbaru 2020/2021 academic year. This research was research and development research using Borg & Gall model. The subjects of this research were media and material experts who tested the validity, chemistry teachers and students (practicality test). Interview and questionnaire were used for collecting the data. The final result was the valid learning media. The result of learning media E-module based on JAS (explore the nature around) approach in supporting student science literature on electrolyte and non-electrolyte solution materials have been tested valid by the media expert was 79% in very valid category and material expert was 89.11% in very valid category. The practical tested by 1 chemistry teacher was 92.5% in very practical category, the practicality tested from 10 students were 88.5% in very practical category. Therefore, it could be concluded that designing and trying out E-module based on JAS (explore the nature around) approach could support student science literature on electrolyte and non-electrolyte solution materials.